On Some Kinds of Constructive Fuzzy Logic - Bolibekyan, Hovhannes R.; Zaslavsky, Igor D. (Mathematical Problems of Computer Science, 2021)
Some modification of the Extended Fuzzy Constructive Logic [14] is considered. It is proved that this modification is actually equivalent to the Intuitionistic Fuzzy Logic introduced in [9].